RNA viruses in the house dust mite Dermatophagoidespteronyssinus, detection in environmental samples and in commercial allergen extracts used for in vivo diagnosis. Issue 12 (21st May 2021) - Vidal‐Quist, José Cristian; Vidal, Carmen; Escolar, Fernando; Lambrecht, Bart N.; Rombauts, Stephane; Hernández‐Crespo, Pedro
Abstract: Background: Allergy to house dust mites (HDM), the most important source of indoor allergens worldwide, is diagnosed and treated using natural extracts from cultures that can contain immunoactive components from the HDM microbiome, including mite‐infecting viruses. This study aimed to contribute to the discovery and characterization of RNA viruses from Dermatophagoides pteronyssinus, followed by their detection in different mite‐derived sources. Methods: Viruses were assembled after in silico metatranscriptomic analysis of D. pteronyssinus RNA samples, visualized by electron microscopy, and RNA detected by direct RT‐PCR or data mining. Mite culture performance was evaluated in vivo . Results: Seven RNA viruses were identified in our laboratory stock colony. Picornavirus‐like viral particles were detected in epithelial cells of the digestive system and in fecal pellets. Most of these viruses could be persistently transmitted to an inbred virus‐free colony by inoculating fecal material from the stock colony. Upon viral infection, no significant effect could be seen on mite population growth. Transcriptomic screening confirmed the presence of homolog sequences to these viruses in independent laboratory stocks of D. pteronyssinus and in other Astigmata mites. Noteworthy, RNA from most of the viruses could be detected by RT‐PCR on house dust samples, reference standards, and/or commercial diagnostic D. pteronyssinus extracts. Conclusions: Our results show that viral infections are common and widespread in D. pteronyssinus, both in natural and culture‐based growth conditions. Potential effects on the mites themselves and consequences toward allergenicity in humans whether exposed naturally or after immunotherapy are discussed. Abstract : Seven RNA viruses were identified in the transcriptome of D. pteronyssinus, being picorna‐like viruses the most abundant. Viral particles are found in epithelial cells of the digestive system, and in fecal pellets from which they can be horizontally transmitted to other virus‐free mites. Viral RNA was detected by RT‐PCR on house dust samples, reference standards, and allergy‐related pharmaceutical products. Abbreviations: AMg, anterior midgut; FDA, food and drug administration; FP, fecal pellet; HDM, house dust mite; Hg, hindgut; PMg, posterior midgut; RNAseq, RNA sequencing; SPT, skin‐prick test; VP, viral particles; WMC, whole mite culture.